2015
DOI: 10.1128/aem.01524-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sewage and Animal Fecal Microbiomes by Using Oligotyping Reveals Potential Human Fecal Indicators in Multiple Taxonomic Groups

Abstract: dMost DNA-based microbial source tracking (MST) approaches target host-associated organisms within the order Bacteroidales, but the gut microbiota of humans and other animals contain organisms from an array of other taxonomic groups that might provide indicators of fecal pollution sources. To discern between human and nonhuman fecal sources, we compared the V6 regions of the 16S rRNA genes detected in fecal samples from six animal hosts to those found in sewage (as a proxy for humans). We focused on 10 abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 53 publications
(113 reference statements)
5
40
0
Order By: Relevance
“…A recent study compared the V6 region of the 16S rRNA gene in fecal samples from six animals to sewage [137]. The authors focused on 10 abundant genera and used oligotyping, which can distinguish ecologically distinct organisms whose rRNA sequences differ from each other by few nucleotides [138].…”
Section: Future Directionsmentioning
confidence: 99%
“…A recent study compared the V6 region of the 16S rRNA gene in fecal samples from six animals to sewage [137]. The authors focused on 10 abundant genera and used oligotyping, which can distinguish ecologically distinct organisms whose rRNA sequences differ from each other by few nucleotides [138].…”
Section: Future Directionsmentioning
confidence: 99%
“…Currently, there is little information available on data acceptance criteria for fecal source identification technologies. The lack of data acceptance criteria is, in part, due to an active method development research community where new technologies are introduced on a regular basis.Fecal source identification technologies are diverse and range from bacterial community approaches (19)(20)(21)(22) to canine scent detection (23), making it difficult to choose the most suitable technology. In this study, the human-associated HF183/BacR287 (24) and HumM2 (25) quantitative real-time PCR (qPCR) methods were selected for data acceptance criteria development.…”
mentioning
confidence: 99%
“…Fecal source identification technologies are diverse and range from bacterial community approaches (19)(20)(21)(22) to canine scent detection (23), making it difficult to choose the most suitable technology. In this study, the human-associated HF183/BacR287 (24) and HumM2 (25) quantitative real-time PCR (qPCR) methods were selected for data acceptance criteria development.…”
mentioning
confidence: 99%
“…Oligotyping, a computational method that makes use of highly variable nucleotide positions in 16S sequences, can distinguish closely related organisms that would normally be classified into one taxon (Eren et al, 2013). Oligotyping has led to the identification of human faecal indicators from multiple taxonomic groups (Koskey et al, 2014;Fisher et al, 2015). Human-specific taxa were found not only in populations of Bacteroidetes, but also in the bacterial phylum Firmicutes, including oligotypes under the genera Blautia, Coprococcus, Dorea, Faecalibacterium and Roseburia (Fisher et al, 2015).…”
mentioning
confidence: 99%
“…Oligotyping has led to the identification of human faecal indicators from multiple taxonomic groups (Koskey et al, 2014;Fisher et al, 2015). Human-specific taxa were found not only in populations of Bacteroidetes, but also in the bacterial phylum Firmicutes, including oligotypes under the genera Blautia, Coprococcus, Dorea, Faecalibacterium and Roseburia (Fisher et al, 2015). In addition, community profiling of pipes transmitting sewage from households to wastewater treatment facilities has shown that Arcobacter species are abundant and prevalent, suggesting that using community composition in pollution source tracking has the potential to detect signatures from urban water infrastructure .…”
mentioning
confidence: 99%